Inculcating Values and Ethics Through Spirituality In The Modern And Stubborn Era - Yanshika Gulati; Dr. Devesh Kumar (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
Employees play the most crucial role in the survival of an organization, where the workforce’s diversity demands adaptability to the growing constraints of the job. This paper explores the impact of spirituality on humanity, specifically within the context of organizational settings. From ancient times, human civilization has been deeply connected with spiritual teachings, such as the Hindu Vedas, which provide profound insights into ethical and moral life conduct. In the modern era, characterized by rapid technological advancements and a prevailing sense of individualism, the role of spirituality in instilling values and ethics becomes even more pertinent. This research investigates how spirituality can be leveraged as a transformative tool to address contemporary organizational challenges, promoting workplace spirituality as an emerging concept crucial for both individual and organizational development. Utilizing a multidisciplinary approach that includes psychology, sociology, religious studies, and philosophy, this study illustrates how spiritual practices contribute to ethical decision-making and foster a harmonious alignment between personal and organizational goals. Key case studies in this paper highlight initiatives where spiritual practices have been successfully integrated into educational systems, corporate governance, and community programs, showing significant improvements in ethical conduct and workplace satisfaction. Moreover, the study addresses potential criticisms regarding the application of spirituality in secular domains, examining how spiritual teachings can coexist with modern values like inclusivity and rationalism. The paper posits that spirituality provides essential nourishment for a calm mindset that aligns with ethical frameworks, proving indispensable for fulfilling moral and ethical principles internally within individuals. Spirituality, when adapted thoughtfully, serves as a bridge between ancient wisdom and contemporary ethical challenges, offering a robust foundation for value education and fostering a positive outlook towards life and work goals in a rapidly changing world.